DEVELOPMENT OF A SELF-DIRECTION GAME HANDBOOK TO IMPROVE INHIBITORY CONTROL FOR 10–12-YEAR-OLDS - Sitaresmi, Dora; Kurniastuti, Irine (Sanata Dharma University Yogyakarta, 2024)
Elementary school-age children need increased inhibitory control to focus and put aside things that are not priorities. Inhibitory control helps children to stay focused, control behavior, think before they act, and manage emotions. However, efforts specifically to increase the ability of inhibitory control have not been made much. This study aims to develop a guidebook to improve inhibitory control in children aged 10-12 years through the game